2020
DOI: 10.1103/physrevb.102.045142
|View full text |Cite
|
Sign up to set email alerts
|

Mott and pseudogap localization in pressurized NbO2

Abstract: We present a detailed study of correlation-induced electronic reconstruction in baddeleyite-type NbO 2 , a distorted ZrO 2-type structure that is found at pressures above 8.0 GPa. Based on density-functional plus dynamical mean-field theory (DFT+DMFT), we stress the importance of multiorbital Coulomb interactions in concert with first-principles band-structure calculations for a consistent understanding of emergent Mottness and pseudogap behavior in pressurized NbO 2 and related d 1 systems. After a proper tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Extensions of the single-site DMFT scheme to explicitly includes inter-site interactions, based, for example, on cluster DMFT approaches, may be considered to describe dynamical dimer-dimer correlations in MoO 2 and related materials. Nonetheless, the good agreement between the frequency dependence of the self-energy (imaginary and real parts) we have recently derived for baddeleyite-type NbO 2 [28] and that of the distorted, body-centered tetragonal (bct) NbO 2 crystal obtained using cluster DFT+DMFT calculations [29], fully qualifies single-site DFT+DMFT approximation for the study of the electrodynamic behaviour of MoO 2 battery material. Here, one-particle LDA density-of-states are computed using the non-fully relativistic version of the PY-LMTO code [30].…”
Section: Introductionsupporting
confidence: 75%
“…Extensions of the single-site DMFT scheme to explicitly includes inter-site interactions, based, for example, on cluster DMFT approaches, may be considered to describe dynamical dimer-dimer correlations in MoO 2 and related materials. Nonetheless, the good agreement between the frequency dependence of the self-energy (imaginary and real parts) we have recently derived for baddeleyite-type NbO 2 [28] and that of the distorted, body-centered tetragonal (bct) NbO 2 crystal obtained using cluster DFT+DMFT calculations [29], fully qualifies single-site DFT+DMFT approximation for the study of the electrodynamic behaviour of MoO 2 battery material. Here, one-particle LDA density-of-states are computed using the non-fully relativistic version of the PY-LMTO code [30].…”
Section: Introductionsupporting
confidence: 75%
“…The MO-IPT scheme is computationally very efficient, with real frequency output at zero and finite temperatures [41], enabling the study of electronic structure reconstruction and transport properties of real materials with different magnetically ordered states and superconducting phase instabilities. Our real frequency MO-IPT scheme [40] has a proven record of good semiquantitative agreements with experiment for a range of correlated materials, and as shown recently it gives results for the spectral functions and self-energies in qualitatively accord with numerical exact continuous-time quantum Monte Carlo (CT-QMC) calculations [42,43], in spite of the fact that fully charged self-consistent DFT+DMFT calculations are presently unreachable within our perturbative treatment. In view of this, below we focus on the correlated spectral functions of paramagnetic CrI 3 bulk crystal and leave the extension of our approach as well as the derivation of the Mott-localized DFT+DMFT band structure for a future work.…”
Section: Resultsmentioning
confidence: 56%
“…This perturbative, many-particle scheme has a proven record of describing MO electronic correlations in broad pband systems [18,[30][31][32][33] and unconventional electronic structure reconstruction induced by dynamical quantum fluctuations in strongly correlated electron systems [34,35]. The MO-IPT scheme is computationally very efficient, with real frequency output at zero and finite temperatures, enabling the study of electronic structure reconstruction of real materials, and as shown recently it gives results for the spectral functions and self-energies in qualitatively accord with numerical exact continuos-time quantum Monte Carlo (CT-QMC) calculations [53,54].…”
Section: Gga + Dmft Model and Resultsmentioning
confidence: 69%